REDUCTION OF WATER CONSUMPTION IN THE PROCESS OF ETHANOL FUEL APPLYING PINCH TECHNOLOGY - Erazo E., R. (2010)
Pinch analysis is applied to reduce energy and water consumption in the process of fuel ethanol production so the technical, economic and environmental feasibility is demonstrated. The consumption of heat, water and total cost of process is reduced to 50, 40 and 25% respectively.